The Role of Digital Transformation in Enhancing Economic Growth in Developing Nations - Martín Paredes; Mariana A. Martínez; Silvina L. Guzman (International Forum of Researchers and Lecturers, 2024)
This paper explores the impact of digital transformation on the economic growth of developing countries. It examines how the adoption of digital technologies such as ecommerce, mobile banking, and digital education can improve productivity, create new markets, and foster inclusive growth. Through a comparative analysis of case studies from various regions, the study highlights the opportunities and challenges faced by developing economies in leveraging digital tools for sustainable development.